STRUCTURE AND SUPERCONDUCTIVITY IN LITHIUM-INTERCALATED NIOBIUM DICHALCOGENIDES - Mcewen, C; Stjulien, D; Edwards, P; Sienko, M (1985)
The series LixNbS2 (0 ≤ x ≤ 0.50) and LixNbSe2 (0 ≤ x ≤ 0.67) have been prepared by high-temperature reaction of Li2S, Nb, and S or Li2Se, Nb, and Se. Structures have been determined by analysis of X-ray powder patterns with polytypism observed in the sulfide series. Evidence of staging and Li ordering is reported, and crystal parameters are proposed for a second-staged sample, Li0.2NbSe2. In the series LixNbSe2, Tc exhibits a monotonic decrease with increasing lithium content, falling to less than 2 K by x = 0.25. In contrast, in the LixNbS2 series, Tc exhibits a more complicated pattern with Tc plummeting to below 2 K by x = 0.05, only to rebound to 3.7 K at x = 0.33 and then fall to below 2 K by x = 0.4. © 1985 American Chemical Society.